2015
DOI: 10.12765/cpos-2015-12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Family Structure and the Experience of Parental Separation: A Study on Adolescents’ Well-Being

Abstract: Large numbers of studies, mostly from the U.S., have addressed the effects of parental separation and divorce, pointing to disadvantages of children and adolescents growing up in separated families. However, evidence on this topic varies across countries and is limited for Germany. Using longitudinal data from waves 1 and 3 of the German Family Panel pairfam, we investigated differences in adolescents’ well-being by comparing stable nuclear families (n = 1968), single mother families (n = 360), and stepfather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
(53 reference statements)
1
8
0
1
Order By: Relevance
“…Similarly, the finding is similar to Walper et al, (2015) who found that parental separation retards the attainment of the children's higher education irrespective of parents' level of education. The between factors in this study also revealed that the self-esteem of the adolescents from separated parents is negatively affected regardless of separated parent's level of education.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similarly, the finding is similar to Walper et al, (2015) who found that parental separation retards the attainment of the children's higher education irrespective of parents' level of education. The between factors in this study also revealed that the self-esteem of the adolescents from separated parents is negatively affected regardless of separated parent's level of education.…”
Section: Discussionsupporting
confidence: 87%
“…The variation in the way they respond to the outcomes of family separation had earlier been attributed to the level of coping ability demonstrated by the adolescents. Walper, et al (2015) maintained that the cause of separation may not be responsible for the outcomes on adolescents' self-esteem but rather pertinent factors that might or might not occur prior to and post separation. This, therefore makes it necessary to investigate whether the self-esteem of in-school adolescents from separated homes will be influenced by the cause of separation (death, divorce, abandonment, work etc).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We controlled for a set of variables which previous research suggested is associated with subjective life satisfaction and happiness (Bjarnason et al, 2012; Levin et al, 2012; Robson, 2010; Walper et al, 2015). Child characteristics considered were age (1 = “11 years old,” 2 = “13 years old,” and 3 = “15 years old”), gender (0 = “male” vs. 1 = “female”), and self‐rated health (1 = “poor,” 2 = “fair,” 3 = “good,” or 4 = “excellent”).…”
Section: Methodsmentioning
confidence: 99%
“…And although adolescents from nonintact families had in general greater difficulties talking to both their mothers and fathers than children from intact families, “children living in joint physical custody ha[d] equal or less problems communicating with their parents than their counterparts in intact families and less such problems than children in other types of nonintact families” (Bjarnason & Arnarsson, 2011, p. 885). Furthermore, previous studies on the association between family structure and adolescents’ life satisfaction or happiness revealed that adolescents from nuclear families reported significantly higher levels of life satisfaction and happiness than adolescents from separated or divorced families did (Bjarnason et al, 2012; Levin et al, 2012; Robson, 2010; Walper, Thönnissen, & Alt, 2015). Again, adolescents living in JPC arrangements after family dissolution felt better than adolescents living in SPC arrangements (Bjarnason et al, 2012; Levin et al, 2012).…”
Section: Introductionmentioning
confidence: 96%